Inhibition of IGF-1R-Dependent PI3K Activation Sensitizes Colon Cancer Cells Specifically to DR5-Mediated Apoptosis But Not to rhTRAIL - Bodvael Pennarun; Jan H. Kleibeuker; Tjitske Oenema; Janet H. Stegehuis; Elisabeth G.E. de Vries; Steven de Jong (Analytical Cellular Pathology)
Background: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) initiates apoptosis in tumor cells upon binding to its cognate agonistic receptors, death receptors 4 and 5 (DR4 and DR5). The activity of the insulin-like growth factor 1 (IGF-1) survival pathway is often increased in cancer, influencing both cell proliferation and apoptosis. We hypothesized that inhibiting the IGF-1 receptor (IGF-1R) using NVP-AEW541, a small molecular weight tyrosine kinase inhibitor of the IGF-1R, could increase death receptor (DR)-mediated apoptosis in colon cancer cells.